The Impact of Self-Efficacy on Performance Management in Malaysia’s Public Sector - MOHAMAD ZAM, RUHANA; AHMAD, SYAHRUL AHMAR; ISMAIL, AIDA MARIA; ISMAIL, AIDA HAZLIN (Information Management and Business Review, 2024)
This study investigates the impact of self-efficacy on performance management within Malaysia’s public sector. Grounded in goal-setting theory, which posits that specific and challenging goals enhance motivation and performance, this research examines how self-efficacy—the belief in one’s ability to execute tasks, influences performance outcomes. Conducted through qualitative in-depth interview sessions with selected participants who are from Tier 1 and Tier 2 staff of the Federal Government of Malaysia, this study provides an in-depth analysis of the relationship between self-efficacy and performance management practices. The study examines how self-efficacy influences performance management in Malaysia’s public sector. Several key findings have arisen from merging the High-Performance Cycle model with Bandura’s self-efficacy theory. The findings emphasize the importance of self-efficacy in improving performance management strategies. Integrating self-efficacy with the High-Performance Cycle model yields concrete solutions for increasing leadership effectiveness and organizational performance. Investing in self-efficacy through focused interventions, coaching, and self-care can greatly improve performance management and help organizations reach their goals more efficiently.